2011
DOI: 10.1088/1741-2560/8/4/046032
|View full text |Cite
|
Sign up to set email alerts
|

Offset prediction for charge-balanced stimulus waveforms

Abstract: Functional electrical stimulation with cuff electrodes involves the controlled injection of current into an electrically excitable tissue for sensory or motor rehabilitation. Some charge injected during stimulation is 'lost' at the electrode-electrolyte interface when the charge carrier is translated from an electron to an ion in the solution. The process of charge injection through chemical reactions can reduce electrode longevity and implant biocompatibility. Conventionally, the excess charge is minimized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The details of the experimental investigation of this system were reported elsewhere [33] and we only present here the equivalent circuit of the electrode-electrolyte interface (Fig.3a) and a final result (Fig.3b). We used Mathworks Simulink to simulate the equivalent circuit of the electrode-electrolyte interface and fit the parameter values given in Table 2.…”
Section: B Electrode-electrolyte Interfacementioning
confidence: 99%
“…The details of the experimental investigation of this system were reported elsewhere [33] and we only present here the equivalent circuit of the electrode-electrolyte interface (Fig.3a) and a final result (Fig.3b). We used Mathworks Simulink to simulate the equivalent circuit of the electrode-electrolyte interface and fit the parameter values given in Table 2.…”
Section: B Electrode-electrolyte Interfacementioning
confidence: 99%
“…This element may or may not be accompanied by a parallel resistor R W . The Warburg element has been used in series with R P resistor [22,23], or as a special case of a Cole compartment (in series with R S ) [11,24,25]. We followed a similar approach presented in [26] and [24] and put two Cole compartments in series with R S to take into account the different materials (i.e., Pt and Ir) in the alloy.…”
Section: Discussionmentioning
confidence: 99%
“…A great deal of cochlear implant-related literature has examined and proposed electrode-tissue interface and EEI models based on platinum electrodes tested in vivo and in vitro using an electrolyte mimicking human perilymph [8][9][10][11][12][13][14][15][16]. These studies characterize and model the EEI using both electrochemical impedance spectroscopy (EIS) and stimulation pulse voltage response (SPVR) data.…”
Section: Introduction 1background and The Study Purposementioning
confidence: 99%
“…Notably, charge‐balanced, biphasic source waveforms, rather than monophasic as used in this study, are used clinically to avoid tissue damage through faradaic (chemical) reactions , although it is likely that a wave that is not charge‐balanced at the electrode would not cause nerve damage in SCS . It may be possible that biphasic stimulation at the frequencies simulated herein produces an altered and partially rectified waveform seen at the target axons under certain conditions, for instance double‐layer capacitance and/or faradaic resistance that is asymmetric around zero voltage . Using the active fiber model we examined the effect of graded rectification on preferential blocking and found that purely biphasic waveforms symmetric about V = 0, that is, with no rectification, do not produce blocking at the amplitudes and frequencies under study, while increasing rectification leads to the blocking effect.…”
Section: Discussionmentioning
confidence: 99%